The battle against disinformation on the coup attempt:: the interplay of post-truth, populism and fact-checking - Cury Luiz, Thiago (2023)
The objective of this paper is to identify the elements of post-truth and populism as well as the sources selected when checking the information classified as “false” by Aos Fatos agency about the attempted coup d’état that took place in Brazil on January 8th, 2023. For this purpose, the methodological apparatus is provided by the case study, according to Yin (2001), with the help of content analysis (BARDIN, 2002), establishing analytical categories and the discrimination of units of analysis. As results, we verified the predominance of fractions of truth and antagonisms, with regard to post-truth and populist rhetoric, and the use of documentary sources, more specifically journalistic, in measuring of the narratives. So, we conclude that fact-checking can improve your measurement strategies in the face of fallacious information, which takes effect in populist rhetoric and explores the post-truth context.